Studi Pegendalian Banjir Di Kecamatan Kepanjen Dengan Sumur Resapan - Rachman, Rizka Aditya; Suhardjono, Suhardjono; Juwono, Pitojo Tri (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2014)
The result of the study show the big of the planning debit system SUB 39 and SUB for the five years period each big are 0.0921 m 3 /second and 0.068 m /second. They found 19 drainage those cannot intercept planning debit at SUB 39 and 14 Drainage at SUB 42. Some cause of accident that cannot intercept the planning debit is that the lack of maintenance and getting many kind of rubbish at the drainage canal. The efforts to handle the drainage that are able to intercept planning debit by making new design the canal dimension and planning individual infiltration well.the form of infiltration well was circle with a diameter 1 m and a depth 3 m by 619 pieces off all infiltration well. Beside handling the design also making the handling recommendation totally about the government wisdoms at that region which should taking part of region societies and resembling to the using societies efficiently in keeping the canal of drainage, developing the well absorption at every home also getting permit in standing building.Keyword: Dainage System, Flood, Infiltration well